Solusi Ekonomi Islam Terhadap Rekayasa Helah (Praktek Riba) - Batubara, Damri (AL-FALAH : Journal of Islamic Economics, 2017)
Islam places economic activity as one of the most important aspects of gaining glory, and therefore economic activity, like any other activity, needs to be controlled and guided in line with the objectives of Islamic Shariah. However, some people take advantage of the legitimate contracts of Islamic law to be able to do usury, or legitimize usury through the engineering of legitimate contracts, or make a legitimate contract as a shield of usury usage called helah (engineering practice usury. If the perpetrator intends to deliberately do helah to justify usury where the first and second sale is not the goal of both parties, but only serve as a tool to justify usury, then no doubt about the prohibition of their actions because a road to the haram is also illegal, because human actions are measured according to their intentions.